Іnfusion-transfusion therapy and inotropic support in patients with sepsis - S. D. Shapoval; S. M. Gritsenko; O. V. Tribushnyi; I. L. Savon (Клінічна хірургія)
Objective. Conduction of retrospective and prospective analysis of the final results of treatment in patients, suffering sepsis on background of complicated diabetic foot syndrome (DFS).